2011
DOI: 10.1117/12.879498
|View full text |Cite
|
Sign up to set email alerts
|

Processing of metals with ps-laser pulses in the range between 10ps and 100ps

Abstract: The potential of pulsed laser system in the range of 10ps to 100ps pulse duration for material processing has been further investigated. In detail the dependency of the volume ablation rate, penetration depth and threshold fluence on the pulse duration and number of pulses applied to the material will be discussed. The experimental results show that in the case of copper and steel, better results in quality and efficiency of the ablated material are achieved with shorter pulse durations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…The pulse duration of these systems is in the range of several 10 ps, (Pierrot et al (2011), Kanzelmeyer et al (2011)). For metals the ablation efficiency significantly drops by about a factor of 5 when the pulse duration is raised from 10 ps to 50 ps as shown by Schmid et al (2011) andJäggi et al (2011), for non metals this drop is less pronounced but still present as shown by Neuenschwander et al (2011).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…The pulse duration of these systems is in the range of several 10 ps, (Pierrot et al (2011), Kanzelmeyer et al (2011)). For metals the ablation efficiency significantly drops by about a factor of 5 when the pulse duration is raised from 10 ps to 50 ps as shown by Schmid et al (2011) andJäggi et al (2011), for non metals this drop is less pronounced but still present as shown by Neuenschwander et al (2011).…”
Section: Introductionmentioning
confidence: 84%
“…Due to incubation effects the threshold fluence also strongly depends on the number of pulses applied, which is described for metals by Schmid et al (2011), Neuenschwander et al (2012, Jee et al (1988) and Mannion et al (2004). Additionally it was found that also the energy penetration depth shows an incubation effect of the same kind.…”
Section: Ablationmentioning
confidence: 93%
See 2 more Smart Citations
“…that there exists a maximum removal rate per average power 1,2 . This maximum depends on the pulse duration 3,4,5,6 whereas shorter pulses lead to higher removal rates. As working at this maximum point usually demands moderate fluences (typically in the range of 1 J/cm 2 or less) multi -spot processing or high speed scanning represent potential technologies to work at high average powers.…”
Section: Introductionmentioning
confidence: 99%